PENTINGNYA LAYANAN BIMBNGAN KONSELING DI SEKOLAH DASAR TERHADAP PERKEMBANGAN PESERTA DIDIK - ulva, retno (Jurnal Ilmiah Ibtida, 2024)
This research aims to determine the importance of guidance and counseling services in elementary schools on student development. This type of research is qualitative using interview instruments. The subjects of this research were four elementary school class teachers. The results of the research show that: (1) It is felt that guidance and counseling services are very important and needed in elementary schools, which are played directly by guidance and counseling teachers to help carry out their developmental tasks, help resolve problems/obstacles experienced so that students can grow as individuals with all their needs. , can actualize themselves, develop their talents, interests and all their potential. (2) Class teachers still have a role as guidance and counseling teachers and need to continue to improve their insight and skills in accompanying and recognizing the characteristics of the needs of students in their class. (3) There are still many problems/obstacles that occur in elementary schools, so collaboration is really needed from class teachers, guidance and counseling teachers, and parents to accompany and guide students in completing developmental tasks well. Keywords: Guidance Counseling Services: Elementary School: Student Development.